'How Much Do I Want the Apocalypse to Happen and Just Wipe this All Clean?': The Use of Apocalyptic Narratives by Non-religious Youth. (19th July 2017) - Cook, Julia
Abstract : Although the ways in which young adults relate to their own futures has been studied at length, the question of how they perceive the long-term, societal future has received comparatively less attention. This article considers how young adults relate to the long-term, societal future with reference to the concept of apocalypse. It draws on an analysis of 28 interviews in which religious and non-religious young adults were asked to discuss their perceptions of the long-term future. By comparing the eschatological depictions cited by religious respondents to the wider sample's views of the future, the findings of this study highlight the presence of a secular apocalyptic narrative. Moreover, while many of the non-religious respondents' understandings of apocalypse were derived from popular culture, this narrative was utilised in ways that extended beyond entertainment-based functions, and could be used to provide insight into the ways in which they related to the societal future.